Pediatric Infect Dis 2019
DOI: 10.36648/2573-0282.4.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Shigella and Salmonella Infections are Associated with Markers of Environmental Enteropathy among Children under Five in Zambia

Abstract: Background: Environmental Enteropathy (EE) is a complex syndrome involving intestinal disorder which has been observed among children living in resource-poor settings. We investigated stored stool samples collected from children under-5 for relationships between specific enteric pathogens and levels of stool EE markers: Calprotectin (CALP), Alpha-1-Anti-Trypsin (AAT) and Myeloperoxidase (MPO). Methods:We used clinical data and stored stool samples collected prior to, and during the early months of widespread r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Shigella detection was associated with the gut inflammatory marker myeloperoxidase (MPO) in 3 recent studies [ 13 , 37 , 38 ]. MPO is an enzyme primarily expressed in neutrophils, which can result in localized tissue damage and inflammation upon activation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shigella detection was associated with the gut inflammatory marker myeloperoxidase (MPO) in 3 recent studies [ 13 , 37 , 38 ]. MPO is an enzyme primarily expressed in neutrophils, which can result in localized tissue damage and inflammation upon activation.…”
Section: Methodsmentioning
confidence: 99%
“…Bona and colleagues (2019) studied Shigella -associated virulence-related genes (VRGs) in Brazilian children, finding that MPO levels were consistently higher in child stool samples positive for 6 VRGs ( ipgB1 , ipgB2 , ospF , sen/ospD3 , virA , and virB ) when compared with children negative for each of these VRGs [ 29 ]. Shigella infections were strongly associated with increased MPO in a secondary analysis of stools from CU5 with clinical symptoms in Zambia [ 37 ]. Also, this study reported strong associations between Shigella spp detections and an overall measure of environmental enteropathy (EE) score (see Table 2 ), further supporting its role in EED.…”
Section: Methodsmentioning
confidence: 99%